Detection of genetic relationships among some species belongs to genus Malus from mid Iraqi regions - AL- Anbari Aseel K; AL-Hadeethi Muazaz A; Jawad. Mohammed M (Tikrit Journal of Pure Science, 2023)
RAPD-PCR method was used for systematic study and revealing the genetic relationships in Malus by using 7 apple cultivars from some mid Iraqi regions, DNA of fresh leaves was extracted using modified protocol of CTAB, 22 prechosen random decamer primers were applied to detect Malus genotypes. four primers gave reproducible and appeared polymorphism in the RAPD profile, a total 48 bands were produced out of which 36 bands were polymorphic, the results arise two main clusters, the first one included Malus sylvestris has unique amplified and discriminated from other Malus taxa, thus it can be a good molecular tool for taxa identification which separated at the similarity value of 0.48, and the second cluster contained two groups, one included M. domestica, and  M. domestica var. ralls janet which appeared as closely related species with a stronger correlation at similarity range of  0.09, furthermore, it considered that the present study identifies reservoir of alleles that useful for breeding programs in parental crosses.